A STUDY OF LINGUISTIC FEATURES OF EXPRESSIONS DENOTING ATTITUDE IN SHORT STORIES BY ALICE MUNRO – THE 2013 LITERATURE NOBEL WINNER - NGUYỄN, THỊ THỦY (đhnn, 2016)
The research aims at finding out the cohesive and semantic features of expressions denoting ‗attitude‘ in English in terms of systematic functional linguistic paradigm for the purpose of implication in teaching and learning English. The data for the study are online collected from the short stories written by Alice Munro, the 2013 Nobel Prize winner on literature. The main methods applied for the research are qualitative, quantitative ones. As to the finding and discussion, first we refer to the view of Halliday M.A.K. and Hassan R. (1994) in order to describe and analyze cohesive features of expressions denoting ‗attitude‘ in Alice Munro‘s short stories in terms of reiteration, lexical relations as cohesive patterns and collocation. In reference to semantic features of expressions indicating ‗attitude‘, we follow the appraisal framework by Martin J.R. and White P.R.R. (2005) in systematic functional linguistic paradigm. In this semantic domain, sub-types of attitude, such as affect, judgment and appreciation have been stated and discussed. We have simultaneously discussed and found the result both qualitatively and quantitatively in order to foster the validity of the research. It is hopefully expected that the result of the study will make a certain contribution to teaching and learning of some related English subjects with regard to the cohesive and semantic features in genral and those of expressions denoting ‗attitude‘ in terms of systematic functional linguistic paradigm in particular.
Keywords: LINGUISTIC FEATURES, EXPRESSIONS DENOTING ATTITUDE .